'Between Law and Transgression: Literature as a (Non-) Civilizing Strategy in the Early 20th Century'. Issue 1 (3rd June 2020) - Kennedy, Kevin
Juxtaposing several strands of European modernism, this article shows how psychoanalysis lays the ground for a transgressive model of literature, which problematizes the widespread early 20 th -century conception of literature as either a civilizing force (articulated in the writings of I.A. Richards and F.R. Leavis) or a tool for freedom of expression (advocated by, amongst others, Ezra Pound). Following a brief analysis of Freud's ideas on transgression in Civilization and Its Discontents, I discuss the work of French Surrealist Georges Bataille, who in the 1930s and 40s developed one of the most wide-ranging accounts of the transgressive potential of literature. Bataille's ideas serve to complement recent accounts of transgressive modernism (notably Rachel Potter's Obscene Modernism ), which tend to focus on transgressive literature as a form of liberation from repressive social, moral and legal constraints. Bataille's Freud-inspired theory, by contrast, points towards a more problematic and ambiguous dimension in the relation between transgression and law, always caught between denial and complicity, and unable to be accommodated within the progressive discourse of legal reform and/or educational progress. I conclude that transgressive literature, in Bataille's sense, functions as an inevitable dialectical counterpoint to any positive conception the socio-ideological function of modern literature.